A Collaborative Model for Managing Animal Hoarding Cases. Issue 3 (3rd July 2019) - Strong, Sandra; Federico, Jennifer; Banks, Ron; Williams, Cathy
ABSTRACT: Companion-animal hoarding is a significant problem in the United States and internationally. Hoarding situations can incubate for years before a case is reported to law enforcement or animal control agencies. According to a survey by Gary Patronek, animal control agencies have estimated there are approximately 3000 reportable cases of animal hoarding annually in the United States. Animal hoarding cases vary in size from fewer than 20 animals to hundreds of animals. Every case of animal hoarding results in suboptimal animal welfare. Wake County, North Carolina, developed a proactive plan for addressing companion-animal hoarding that implemented a team approach to assist animals at risk, hold people accountable, address the mental health component of this problem, and create a more humane community. The plan involved animal control officers, crisis intervention counselors, law enforcement officers, veterinarians, veterinary technicians, and animal rescue partners. This intervention strategy was implemented in 2015, and cases were tracked to document animal outcomes. The conclusion of this experience is that a diverse team approach can best address the animal and human welfare challenges and the environmental concerns associated with animal hoarding.